RANCANG BANGUN CONVERTER KIT SEBAGAI ALAT KONVERSI ENERGI SEPEDA MOTOR 100cc BERBAHAN BAKAR GAS LPG - Setiawan, Rizal Justian; Fitrihartanta, Muhammad Sahid; Mujiono, Mujiono; Nurhadiyanto, Didik (Injection: Indonesian Journal of Vocational Mechanical Engineering, 2021)
The natural gas potential in Indonesia can be used to support the renewability of alternative fuels for motorcycles.LPG (Liquefied Petroleum Gas) is one of the Gas Fuel products that can be used as fuel to replace the use of OilFuel. Therefore, an energy conversion tool is needed to utilize LPG as a motorcycle energy source. The purposeof this research is to design and manufacture a gas motor converter kit. This converter kit has three technologies,such as 1) a fuel distribution system that uses a manual fuel faucet so that the fuel distribution process is better,2) there is a solenoid valve that functions to cut off gas flow when the vehicle stop without removing the regulatoron the fuel tube, and 3) the position of the gas fuel tube is under the motorcycle seat so that it is safer. The researchmethod using VDI2221 (Verein Deutcher Ingenieure). The research result is the creation of converter kits thatare made through the design process, turning process, milling process, welding process, and assembling process.The research conclusion obtained is that the converter kits that have been made can be implemented on 100ccmotorcycles, and no leaks or defects were found in the converter kits, so the tool can be used properly on 100ccmotorcycles.